Automatic creation of TV content to integrate in seniors viewing activities - Reis, L. (2017)
The challenges and opportunities that arise with the increase of older populations are drawing the attention of several sectors of society, as is the case of the technological segment. The development of technical solutions to improve seniors’ quality of life and promote their autonomous living is commonly found in the roadmap of research teams and companies. Reports and news show that the elderly feel several limitations and problems concerning the activities of finding and accessing credible information through technical solutions. Statistics and studies also reveal that older people have high levels of daily television consumption, which makes TV one of the ways with a lot of potential to inform seniors. Taking in consideration these two factors, it seems that information broadcast to elderly through television, without requiring a search activity, may be an idea with a lot of potential. In line with this, this paper reveals the process to define audio-visual content for seniors as well as a set of guidelines for the development of iTV platforms for this target group. Seniors’ preferences concerning the sound and text elements were gathered in two different moments in two different Senior Universities in Portugal.